Sex-specific neural activity when resolving cognitive interference in individuals with or without prior internalizing disorders. (30th March 2016) - Wang, Zhishun; Jacobs, Rachel H.; Marsh, Rachel; Horga, Guillermo; Qiao, Jianping; Warner, Virginia; Weissman, Myrna M.; Peterson, Bradley S.
Abstract: The processing of cognitive interference is a self-regulatory capacity that is impaired in persons with internalizing disorders. This investigation was to assess sex differences in the neural correlates of cognitive interference in individuals with and without an illness history of an internalizing disorder. We compared functional magnetic resonance imaging blood-oxygenation-level-dependent responses in both males ( n =63) and females ( n =80) with and without this illness history during performance of the Simon task. Females deactivated superior frontal gyrus, inferior parietal lobe, and posterior cingulate cortex to a greater extent than males. Females with a prior history of internalizing disorder also deactivated these regions more compared to males with that history, and they additionally demonstrated greater activation of right inferior frontal gyrus. These group differences were represented in a significant sex-by-illness interaction in these regions. These deactivated regions compose a task-negative or default mode network, whereas the inferior frontal gyrus usually activates when performing an attention-demanding task and is a key component of a task-positive network. Our findings suggest that a prior history of internalizing disorders disproportionately influences functioning of the default mode network and is associated with an accompanying activation of the task-positive network in females during the resolution of cognitive interference. Highlights: Few fMRI studies examine sex differences in cognitive interference. We examined individuals with and without a history of mental illness (internalizing disorders). Females compared to males deactivated more in the regions of the task-negative, or default mode, network. Females with a history of illness compared to males with an illness history deactivated more in the task-negative network, but also activated more in the task-positive network.